Relación entre las concepciones de evaluación de las pruebas externas con la evaluación propuesta en el PEI de la Institución Educativa Presbítero Luis Eduardo Pérez Molina y Colegio Cooperativo Simón Bolívar en el municipio de Barbosa (Ant.) (2016)
This document relates an intinerary by different models and regulation that have base on the assessment conception of learning in the basic and middle education in the colombian context; in this intinerary a special recognition is done to the importance given to external tests, to a relating level as well as the assessment systems of the educational institutions Presbitero Luis Eduardo Pérez Molina and Colegio Cooperativo Simón Bolívar in Barbosa a town in antioquia. This research is developed from a documental approach motivated by the correspondence that there is between regulations and the way they are recognized in the researched institutions and the coherence among the components in the area of academic and pedagogical gestion. This analysis let us identify the relationship between the conceptions of internal assessment in the mentioned institutions and the external tests and how the analysis of results contributes to the qualification of academic processes. It is desired to investigate the line of internal and external assessment that take us to grow up in and for life itself from diagnosis, formative, democratic, integral and summary aspect. Grupo de Investigación: Interdisciplinario de Estudios Pedagógicos (GIDEP). -- Línea de Investigación: Pedagogías Críticas. -- Área: educación. -- Tema: evaluación del aprendizaje.